2000
DOI: 10.1161/01.str.31.6.1210
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Induced Cortical Reorganization After Stroke in Humans

Abstract: Background and Purpose-Injury-induced cortical reorganization is a widely recognized phenomenon. In contrast, there is almost no information on treatment-induced plastic changes in the human brain. The aim of the present study was to evaluate reorganization in the motor cortex of stroke patients that was induced with an efficacious rehabilitation treatment. Methods-We used focal transcranial magnetic stimulation to map the cortical motor output area of a hand muscle on both sides in 13 stroke patients in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

50
634
5
39

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,229 publications
(744 citation statements)
references
References 67 publications
50
634
5
39
Order By: Relevance
“…16,26 Similar motor map expansions have been detected in stroke patients treated with constraint-induced movement therapy, where use of the impaired arm and hand is encouraged by limiting use of the non-affected limb. 27 Notably, these studies assessed cortical reorganization long after rehabilitation had commenced and thus it remains unclear whether behavioral recovery coincides temporally with the formation of new somatosensory maps. Interestingly, we previously showed that ischemic rats exposed to ER begin to exhibit enhanced functional recovery as early as 14 days after onset of ER, 3 temporally corresponding with our current findings of increased neuronal activation in periinfarct cortex after 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…16,26 Similar motor map expansions have been detected in stroke patients treated with constraint-induced movement therapy, where use of the impaired arm and hand is encouraged by limiting use of the non-affected limb. 27 Notably, these studies assessed cortical reorganization long after rehabilitation had commenced and thus it remains unclear whether behavioral recovery coincides temporally with the formation of new somatosensory maps. Interestingly, we previously showed that ischemic rats exposed to ER begin to exhibit enhanced functional recovery as early as 14 days after onset of ER, 3 temporally corresponding with our current findings of increased neuronal activation in periinfarct cortex after 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…16 Nevertheless, this result should be viewed with caution, especially because the robot group did not show improvements in the proximal Fugl-Meyer test over this same 6-month period, and the FIM instrument does not penalize subjects who perform activities using compensation with the less affected limb. Future studies should consider the Motor Activity Log, [5][6][7][8][9] which assesses the actual amount of use of the more affected limb in ADLs and the quality of movement. It would also have been useful to determine if the group differences at the 6-month point were retained 1 year after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] This therapy involves intensive repetitive exercise of the more affected limb coupled with constraint of the opposite limb and results in positive cortical reorganization in the motor cortex. 8 In less severely impaired stroke subjects, simple repetitive exercise may be superior to other types of therapy. CIT has recently been shown to have advantages relative to neurodevelopmental treatment of equal intensity.…”
mentioning
confidence: 99%
“…These results were also verified by Wisneski andJohnson 2006, 2007) for complex ADLs such as drinking and eating. Successful examples of novel task-oriented therapy are forced-use and Constrained-Induced Movement Therapy (CIMT) (Taub et al 1994;Taub et al 1999;Sterr et al 2000;Liepert et al 2002;Page et al 2004;Aycock et al 2004). The training is intense and repetitive, requiring the use of the impaired arm.…”
Section: Introductionmentioning
confidence: 99%
“…The training is intense and repetitive, requiring the use of the impaired arm. Data indicate that CIMT therapies reduce learned non-use, increase ADL function, and often increase the size and change the location of the cortical area representative of a muscle function (Liepert et al 2002). These forced-use therapies often induce changes in the motor areas especially in the motor cortex and the cerebellum.…”
Section: Introductionmentioning
confidence: 99%